O duszy wczoraj i dziś: Panorama wybranych poglądów filozoficznych i teologicznych = On the Soul : An Overview of Selected Philosophical and Theological Concepts, Past and Present - Nadbrzeżny, Antoni (Verbum vitae, 2022)
The paper briefly discusses selected philosophical and theological interpretations of the soul which have appeared throughout intellectual history, starting from antiquity and up until modern times. The paper is, by definition, a kind of general introduction to more detailed studies on the existence, origin and nature of the soul. Presenting a wide range of viewpoints, the author employs a chronological framework in order to show the historical development of the various views about the soul: (1) prehistoric and extra-biblical ancient concepts of the soul; (2) the biblical understanding of the soul; (3) patristic concepts of the soul; (4) medieval concepts of the soul; (5) modern concepts of the soul; (6) contemporary views on the soul; and (7) reinterpretations of the soul in present-day Catholic theology. Thus, in addition to highlighting the differences and similarities between the older, traditional formulations regarding the soul, the work also provides an overview of contemporary reinterpretations.